Unmanned aerial vehicle with night vision for tracking intruder - Dhinesh, Ramotharan (2015)
Nowadays there are a lot of theft are happening everywhere and it is dangerous for a person to chase after the intruder because maybe the intruder might have a weapon and harm us. There wasn’t any other way to track the intruder other than chasing to in-form the authority the location where the intruder is. The aim of this project is to find one of the solutions to overcome this project by using Unmanned Aerial Vehicle (UAV) with night vision camera for tracking the intruder. This project mainly focus on the amount of ground light intensity needed and the distance of night vision camera which placed on UAV can detect the shadow of intruders. Besides that, to investigate whether the UAV can detect the intruders with the following path it travels with a specific amount of ground light. Last but not the least, to investigate does the UAV interrupts the signal, data transfer and clear image of intruder using the night vision camera. The experimental result will be analysed.